2017
DOI: 10.1111/ddg.13191
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept, adalimumab, and ustekinumab in psoriasis: analysis of 209 treatment series in Austria

Abstract: Most AEs occur during the first year of treatment. Adalimumab and ustekinumab are marked by longer drug survival compared to etanercept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Thus, it might be more useful for the clinician than the mere comparison of PASI score changes during treatment. Psoriasis drugs are usually discontinued for three reasons: lack of primary efficacy, loss of efficacy and AEs . More than half of our patients discontinued apremilast treatment, and most did so because of the lack of primary efficacy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, it might be more useful for the clinician than the mere comparison of PASI score changes during treatment. Psoriasis drugs are usually discontinued for three reasons: lack of primary efficacy, loss of efficacy and AEs . More than half of our patients discontinued apremilast treatment, and most did so because of the lack of primary efficacy.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with mild disease can often be treated efficiently with topical preparations; however, those with moderate to severe disease require systemic therapies including photo (chemo) therapy with UVA and UVB, fumaric acid esters, retinoids, methotrexate, cyclosporine, or newer biologic agents (biologics) and their biosimilars . Such biologics have changed the therapeutic landscape, and most patients benefit greatly from these new modalities . Still, not all patients respond to such systemic antipsoriasis therapies.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was estimated in a multivariable model, in which sex was not being studied as the main exposure, thus it should be interpreted with caution (26). Similarly, Richter et al (27) identified male sex as a positive predictor of longer adalimumab survival in psoriasis, and Pogácsás et al (28) observed more long-term survival of TNF-alpha inhibitors and ustekinumab amongst men in a Hungarian cohort. Given the differences in methodologies, further prospective studies should be carried out to measure the impact of sex on the effectiveness of systemic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes (mainly PASI) were reported in 75% of prospective studies [27, 39, 47-53], in about 50% of prospective registries [20, 24, 54-61] and retrospective studies [29, 30, 32, 34, 37, 62-70], and in no retrospective administrative databases/claims. Drug survival of biological therapies was reported in over 60% of prospective registries [14, 20, 21, 24, 25, 31, 54, 57, 71-74], retrospective studies [18, 19, 22, 23, 26, 29, 30, 32, 34, 37, 38, 68, 70, 75-77] and administrative databases/claims [28, 35, 36, 40-42, 46], and less frequently (33%) in prospective studies [27, 33, 52, 78]. Subanalyses on reasons of discontinuation, such as switching, dose augmentation, or biological therapy restarting, were scanty.…”
Section: Resultsmentioning
confidence: 99%